Adoption of Digital Marketing Strategies by Medical Schemes in South Africa: A Case Study of Two Large Open Medical Schemes - Willie, Michael Mncedisi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines how digital marketing strategies—mobile apps, social media, and e-mail marketing—enhance consumer engagement, retention, and trust within the health insurance sector. Research Design and Methodology: Using purposive sampling, a case study approach was employed to analyze two health insurance schemes (Scheme A and B). Data collection focuses on mobile app usage, social media engagement, and e-mail campaigns. Findings and Discussion: Scheme A saw an 85% increase in daily app logins and a 14% rise in social media followers. Meanwhile, Scheme B experienced a 39% growth in app downloads but lower social media engagement. Both schemes demonstrated a shift from e-mail marketing to mobile and social media platforms. Implications: Health insurers should prioritize mobile and social media marketing to enhance customer engagement and loyalty through personalized digital interactions. The study contributes to understanding digital marketing's role in the industry and provides insights for future research.